Positivity at test of cure following first-line treatment for genital Mycoplasma genitalium: follow-up of a clinical cohort. (5th August 2014) - Gundevia, Zarin; Foster, Rosalind; Jamil, Muhammad Shahid; McNulty, Anna
Abstract : Objectives: To describe antibiotic use for treatment of Mycoplasma genitalium (MG) at an urban sexual health centre in Australia. To describe MG positivity rates in those returning for 1 month test of cure (TOC) following first-line antibiotic treatment for MG. Methods: Retrospective cross-sectional case-note review for all patients diagnosed with MG at Sydney Sexual Health Centre from 2009 to 2013. Results: Two hundred and eighteen MG cases were identified; 66% were male and 90% were symptomatic at presentation. Four people did not return for treatment. Azithromycin containing regimens were prescribed as first-line treatment in 88% of cases; azithromycin 1 g stat in 75% of cases and a course of extended azithromycin 1 g stat plus 500 mg daily for 4 days in 14% of cases. TOC was performed in 53% (95% CI 46% to 60%) of cases and 28% (95% CI 20% to 38%) of these cases were MG-positive at TOC. Of those having a MG-positive result at TOC, 26% received azithromycin 1 g stat and 33% received extended azithromycin. Accounting for cases lost to follow-up in azithromycin containing regimens, the positive MG TOC rate was estimated to be between 15% and 61%. Conclusions: High rates of MG positivity were found in those attending TOC following first-line treatment of MG with azithromycin containing regimens.